The Rescuing of Muslim Anthropological Thought (American Journal of Islam and Society, 1987)
Akbar S. Ahmed, Toward Islamic Anthropology: Definition, Dogma, andDirections, Islamization of Knowledge series (2) New Era Publications/InternationalInstitute of Islamic Thought 1976, 77 pp.Talal Asad, The Idea of an Anthropology of Islam, Center for contemporaryArab studies, Georgetown University, Washington, D.C. 1986, 22 pp.I. The Malaise and its RemedyBoth of these scholarly publications may be seen as statements of the needfor Islamic anthropology. They contain expressions of the discontent of Muslinanthropologists with the state of the art of contemporary anthropological studies.Many Muslim anthropologists and other social scientists share in the feelingsevident in these essays and well stated in the late Dr. Ali Shari'ati's Civilizationand modernization:When I feel my own religion, literature, emotion, needs and painsthrough my awn culture, I feel my own self, the very social and historical ...